EPISTOLARY AUTHORITY IN EARLY MODERN JAVA: A PHILOLOGICAL AND HISTORICAL ANALYSIS OF MATARAM’S ADMINISTRATIVE LETTERS TO SOUTHERN CIREBON, LATE SEVENTEENTH CENTURY - Barry Sandy Sadewo; Mochammad Wibisono; Noor Ali; Fitriyani Fitriyani (Tunas Harapan Ummat Foundation, 2026)
This study examines how authority and official instruction were articulated in a set of administrative letters issued by the Sultanate of Mataram to Cirebon in 1687. Using a philological approach, it combines codicological observation, linguistic analysis, and historical contextualization to reconstruct the communicative strategies embedded in the manuscripts. Close reading of orthography, formulaic expressions, and material features reveals consistent patterns in how directives were framed and transmitted. The analysis shows that these letters functioned not merely as administrative records, but as instruments through which political authority was asserted and negotiated. Beyond conveying legal and procedural instructions, they reinforced hierarchical relations between Mataram and local rulers, while also signaling expectations of compliance. Variations in linguistic register and textual form suggest a deliberate effort to calibrate tone and authority according to context. This study is based on a limited number of surviving manuscripts, and its findings are shaped by gaps in preservation, scribal variation, and inconsistencies in language use. While these constraints limit broader generalization, they also highlight the need for careful, text-based analysis in reconstructing early modern political communication. By situating Mataram’s correspondence within its historical and material context, this article contributes to ongoing discussions in Javanese historiography, manuscript studies, and the history of governance in early modern Southeast Asia. It also points to the value of integrating philological methods with comparative and digital approaches in future research.